2018
DOI: 10.1186/s40594-018-0128-1
|View full text |Cite
|
Sign up to set email alerts
|

Student, instructor, and observer agreement regarding frequencies of scientific teaching practices using the Measurement Instrument for Scientific Teaching-Observable (MISTO)

Abstract: Background: The Scientific Teaching (ST) pedagogical framework encompasses many of the best practices recommended in the literature and highlighted in national reports. Understanding the growth and impact of ST requires instruments to accurately measure the extent to which practitioners implement ST in their courses. Researchers have typically relied on students, instructors, or observers to document course teaching practices, but it remains unclear whether and how these perspectives differ from each other. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 51 publications
6
25
0
Order By: Relevance
“…Teacher observation scores (RTOP) were positively correlated with MIST composite scores across both groups of faculty (Figure 4). A recent study also found high agreement between instructor and student perceptions of scientific teaching (Durham et al 2018). Our findings suggest that MIST may be an informative proxy for gauging the learner-centeredness of a course.…”
Section: Student Perceptions Reflect Teaching Practicessupporting
confidence: 75%
See 1 more Smart Citation
“…Teacher observation scores (RTOP) were positively correlated with MIST composite scores across both groups of faculty (Figure 4). A recent study also found high agreement between instructor and student perceptions of scientific teaching (Durham et al 2018). Our findings suggest that MIST may be an informative proxy for gauging the learner-centeredness of a course.…”
Section: Student Perceptions Reflect Teaching Practicessupporting
confidence: 75%
“…Students perceptions of learner-centered teaching practices can vary (Machemer and Crawford 2007, Cavanaugh 2011, Durham et al 2018. The Measurement Instrument for Scientific Teaching confirms results from the ATI and RTOP, that FIRST IV faculty are teaching more student-centered courses than Comparison faculty (Table 3).…”
Section: Student Perceptions Reflect Teaching Practicessupporting
confidence: 58%
“…We conducted analyses to understand to what extent these survey data were consistent with each belief. The beliefs we investigate center on the usage of active learning, which we measure via instructor self-report of how class time is spent [ 11 , 17 ]. In particular, we use the reported percentage of class time spent with students “listening to the instructor lecture or solve problems” (i.e., “in lecture”) as a proxy for the percentage of class time spent in non-active learning activities, following others in lumping together various active learning strategies for comparison to traditional didactic lecture [ 5 , 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…Because we are interested in the transition from high school to college, we observed the first four to five class periods each instructor taught using the COPUS (Smith et al, 2013). Although previous studies using classroom observations have used two to three class periods either over 1 week of a course or from different points in the semester (Smith et al, 2014;Lewin et al, 2016;Durham et al, 2018;Pelletreau et al, 2018), four class periods have been found to reflect variation in an instructor's teaching practices (Stains et al, 2018). For courses with one instructor, the class periods were all at the beginning of the semester, excluding the first day of class, which typically includes a higher level of the administration code.…”
Section: Classroom Observationsmentioning
confidence: 99%